Optimization and experimental verification of coplanar interdigital electroadhesives. (16th September 2016) - Guo, J; Bamber, T; Chamberlain, M; Justham, L; Jackson, M
Abstract: A simplified and novel theoretical model for coplanar interdigital electroadhesives has been presented in this paper. The model has been verified based on a mechatronic and reconfigurable testing platform, and a repeatable testing procedure. The theoretical results have shown that, for interdigital electroadhesive pads to achieve the maximum electroadhesive forces on non-conductive substrates, there is an optimum electrode width/space between electrodes (width/space) ratio, approximately 1.8. On conductive substrates, however, the width/space ratio should be as large as possible. The 2D electrostatic simulation results have shown that, the optimum ratio is significantly affected by the existence of the air gap and substrate thickness variation. A novel analysis of the force between the electroadhesive pad and the substrate has highlighted the inappropriateness to derive the normal forces by the division of the measured shear forces and the friction coefficients. In addition, the electroadhesive forces obtained in a 5 d period in an ambient environment have highlighted the importance of controlling the environment when testing the pads to validate the models. Based on the confident experimental platform and procedure, the results obtained have validated the theoretical results. The results are useful insights for the investigation into environmentally stable and optimized electroadhesives.